Numerical study of eddy current by Finite Element Method for cracks detection in structures - S. Harzallah; M. Chabaat; K. Chabane (Fracture and Structural Integrity)
In this paper, we try to use the finite element method of 2-D axisymmetry to solve problems in eddy current testing problems where the main idea is detecting crack's shape using the NDT-EC. Results are given for a simple eddy current problem using the finite element method as a tool to control cracks and defects in materials and eventually, to study their propagation as well as their shape classification. These latest can be described as the task of reconstructing the cracks and damage in a tube’s profile of an inspected specimen in order to estimate its material properties. This is accomplished by inverting eddy current probe impedance measurements which are recorded as a function of probe position. This approach has been used in the aircraft industry to control cracks. Besides, it makes it possible to highlight the defects of parts while preserving the integrity of the controlled products.